Importance of immunization in chiderns: A sweeping knowledgeable review - Salvi, Jayshree (Indian Journal of Nursing Sciences, 2024)
Immunization is considered as the most cost effective and safest public health intervention to reduce childhood morbidity and mortality although its full potential is not reached yet. Many under five children die from vaccine preventable diseases (VPD’s) each year. The burden of infectious diseases has been reduced primary due to immunization. Life expectancy is also increased due to vaccination. Immunization prevents diseases like diphtheria, measles, pertussis, pneumonia, polio, rotavirus diarrhoea, rubella, tetanus and many more. The immunization can be achieved by two forms they are active immunization and passive immunization. Vaccination is the active form of immunization. Active immunization entails the introduction of a foreign pathogenic micro organism enters into the body which causes the body itself to generate immunity against the target. This immunity comes from the T-cells and B –cells with their anti-bodies. Passive immunization is where pre-synthesized elements of immune system are transferred to a person so that the does not need to produce these elements itself. Passive immunization occurs physiologically, when antibodies are transferred from mother of fetus during pregnancy to protect the fetus before and shorting after birth. Artificial passive immunization is normally administrated by injection and is used if there has been a recent outbreak of a particular disease or as an emergency treatment for toxicity, as in for tetanus. Knowledge is necessary to take any decision. Mothers’ knowledge can help them to take proper decision regarding immunization of her child. Keeping these facts, we did a systematic review with the objective to assess the knowledge about immunization of under five children among mothers and to impart health education to mothers regarding childhood immunization.